(3eaGgje hefGXQGJ aj EOGQI GdJZjQs - (3OGajO(B, (3hjdShfs ((3GdbGgQI(B:s (3OGQ GdaLQ ddfTQ h GdJhRjY(B,s, 2002)
(3JLO aj gPG GdcJGH (B: (3GSJQGJLjI GdJZjQ , JYGQV GdeOGNd GdJMdjdjI ddJZjQ GdJfXjej , YedjGJ GdJZjQ GdeNWW aj ebGHd YedjGJ GdJZjjQ GdYahj , Jchjf hJfajP GdJZjjQ GdESJQGJLj , GdKbGaI GdJfXjejI hGdJZjQ , GdeOGNd GdeHQeLI ddJZjQ GdJfXjej ,GSJQGJLjI GdJZjQ , HYV GdfJGFL GdNJGejIs
(3GdeQGLY U(B.214s
Keywords: (3EOGQI GdJZjQs